The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-33482-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Caesarean Section on the Risk of Childhood Overweight and Obesity: New Evidence from a Contemporary Cohort Study

Abstract: Caesarean section (CS) rates are increasing globally and exceed 50% in some countries. Childhood obesity has been linked to CS via lack of exposure to vaginal microflora although the literature is inconsistent. We investigated the association between CS birth and the risk of childhood obesity using the nationally representative Growing-Up-in-Ireland (GUI) cohort. The GUI study recruited randomly 11134 infants. The exposure was categorised into normal vaginal birth (VD) [reference], assisted VD, elective (plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 46 publications
4
46
1
Order By: Relevance
“…Additionally, ndings from this study suggested caesarean section delivery as risk factor for childhood obesity, which is consistent with a prospective cohort study in the literature that reported a ve-fold higher odds of childhood obesity associated with caesarean delivery [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, ndings from this study suggested caesarean section delivery as risk factor for childhood obesity, which is consistent with a prospective cohort study in the literature that reported a ve-fold higher odds of childhood obesity associated with caesarean delivery [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…A summary of the search process is illustrated in Figure 2, as recommended by the PRISMA guidelines [90]. Due to sufficient data regarding the occurrence of respiratory tract infections, asthma, overweight/obesity as well as diabetes mellitus type 1, 16 articles [11,20,67,68,[70][71][72][73][74][75][76][77][78][79][80][81]85,86,88,89] were included in the meta-analysis. for those citations considered potentially relevant and assessed for eligibility by the two researchers.…”
Section: Study Selection Processmentioning
confidence: 99%
“…Several studies have identified the presence of different intestinal microbial profiles between vaginally delivered and cesarean section delivered babies [26], with a lower microbiome richness and diversity among infants born by elective cesarean section compared to those born vaginally [26].…”
Section: Introductionmentioning
confidence: 99%